3
$\begingroup$

I want to compute the mass of AdS schwarzschild by ADM mass formula but I could not find where I am wrong. AdS schwarzschild line element is : $$ ds^2 =-f dt^2 +\frac{dr^2}{f} +r^2 d\sigma^2_{d-1} $$ where: $$ f=k+\frac{r^2}{L^2}-\frac{\omega^{d-2}}{r^{d-2}} $$ ADM mass formula is $$ M=\int (k-k_0)\sqrt{\sigma}d^{d-1}x $$ $k$ is extrinsic curvature of $S_{t=cte,r=cte}$ and $k_0$ the extrinsic curvature $S_{t=cte,r=cte}$ in pure AdS. $$ k=\sigma^{\alpha\beta}k_{\alpha\beta}=\frac{1}{r^2}\Gamma^r_{\alpha\beta}n_r $$ $n$ is normal vector to the surface $r=cte$, $n_\alpha=(\frac{1}{\sqrt{f}},0,...,0)$. $$ k=\frac{1}{r^2}\frac{1}{2}g^{rr}\partial_rg_{\alpha\beta}\frac{1}{\sqrt{f}}=\frac{\sqrt{f}}{r} $$ $k_0$ has the same relation of $k$ but $f=k+\frac{r^2}{L^2}$. $$ M=\lim _{r->\infty}\int (k-k_0)\sqrt{\sigma}d^{d-1}x=V_{d-1} r^{d-1} (\frac{\sqrt{k+\frac{r^2}{L^2}-\frac{\omega^{d-2}}{r^{d-2}}}}{r}-\frac{\sqrt{k+\frac{r^2}{L^2}}}{r})=V_{d-1} r^{d-1} L((1+\frac{kL^2}{r^2}-\frac{\omega^{d-2}L^2}{r^d})^{\frac{1}{2}}-(1+\frac{kL^2}{r^2})^{\frac{1}{2}}=V_{d-1} r^{d-1}L (-\frac{\omega^{d-2}L^2}{r^d})=\lim_{r->\infty}V_{d-1} L (-\frac{\omega^{d-2}L^2}{r})=0 $$ I dont know where it is wrong.

$\endgroup$

1 Answer 1

0
$\begingroup$

I think the issue is that you’re using a formula for the ADM mass which assumes unit lapse. Consider a spherically symmetric spacetime of the form \begin{align} {\rm d}s^2 & = -f(r) \, {\rm d}t^2 + h(r)\, {\rm d}r^2 + r^2 ({\rm d}\theta^2 + \sin^2\theta\, {\rm d}\varphi^2) \end{align}

From the outward pointing unit normal 3-vector $(s^r,s^\theta,s^\varphi)=(h(r)^{-1/2},0,0)$ we compute the trace of the extrinsic curvature, \begin{align} k & = D_i s^i \\ & = \partial_r s^r + (\Gamma^r_{rr}+\Gamma^\theta_{\theta r} + \Gamma^\varphi_{\varphi r})s^r \\ & = -\frac{1}{2}\frac{h’(r)}{h(r)^{3/2}} + \left[\frac{h’(r)}{2h(r)} + \frac{1}{r} + \frac{1}{r}\right]\frac{1}{\sqrt{h(r)}} \\ & = \frac{2}{r}\frac{1}{\sqrt{h(r)}} \end{align}

Specializing to the case of Schwarzschild-AdS$_4$, \begin{align} f(r) & = 1 - \frac{2m}{r} + a^2 r^2 \\ h(r) & = \frac{1}{1 - \frac{2m}{r} + a^2 r^2} \end{align} we obtain \begin{align} k & = \frac{2}{r}\left(1-\frac{2m}{r}+a^2r^2\right)^{1/2} \\ k_0 & = \frac{2}{r}\left(1 + a^2 r^2\right)^{1/2} \end{align} The ADM mass is \begin{align} M_{\rm ADM} & = -\frac{1}{8\pi}\int {\rm d}^2 x \sqrt{\sigma} N(k-k_0) \\ & = -\frac{1}{8\pi} \lim_{r\to\infty} (4\pi r^2) \left(1 - \frac{2m}{r} + a^2 r^2\right)^{1/2} \frac{2}{r}\left[\left(1 - \frac{2m}{r} + a^2 r^2\right)^{1/2} - \left(1 + a^2 r^2\right)^{1/2}\right] \\ & = m \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.